Towards a Phygital Experience: Analyzing the Role of Virtual Tourism in the Attractiveness of Island Territories - Turki Makni, Amal (Journal of Digital Marketing and Communication, 2025)
ABSTRACT: Islands faced challenges related to tourism dependence and the fragility of their ecosystems. Virtual tourism (VT) emerged as an innovative solution, extending and enriching the tourist experience while reducing pressure on physical sites. This research examined the role of VT as a lever for phygital marketing, aiming to increase the attractiveness of island destinations while supporting their sustainability. It adopted a multi-stakeholder qualitative approach, combining semi-structured interviews with tourists and managers to capture perceptions, practices, and interactions related to VT. The results showed that VT enriched the tourist experience, fostered emotional and cognitive engagement, facilitated interactions with local stakeholders and other visitors, and contributed to more sustainable and responsible tourism. This study highlighted concrete recommendations allowing tourism professionals to integrate VT into the enhancement of island destinations by supporting the development of an innovative, responsible, and sustainable phygital experience.